Peningkatan Omset Usaha Laundry Melalui Penerapan Akuntansi Dan Digitalisasi Marketing - Markonah, Markonah; Yohanes Ferry Cahaya; Saripudin, Saripudin; Suharyanto, Suharyanto; Desmar Panji Suryananto (Jurnal Abdimas Perbanas, 2024)
This community service aims to increase the turnover of MSME Laundry players, especially Aspact Laundry Partners. First, with the development of digital-based automatic washing machines, the aim is to bring innovation to the laundry industry, introducing modern technology to improve efficiency and service quality.   This washing machine offers ease of use, better control, and the ability to wash more laundry with better results. With a size suitable for various sizes of laundry businesses, this washing machine can increase productivity and enable entrepreneurs to manage their operations more effectively. Apart from that, training was also held on financial reports and digital marketing to expand the market and in turn increase turnover. It is hoped that the implementation of these digital-based automatic washing machines will provide significant benefits to target partners, helping them to compete in an increasingly competitive market and increasing their customer satisfaction.